Lithium nickel-containing composite oxide, positive electrode active material for lithium ion secondary battery using the lithium nickel-containing composite oxide as a base material, and method for producing the same

JP7630559B2Active Publication Date: 2025-02-17SUMITOMO METAL MINING CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023105447
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2025-02-17
Estimated Expiration
2038-11-29

Smart Images

  • Figure 0007630559000002
    Figure 0007630559000002
  • Figure 0007630559000003
    Figure 0007630559000003
  • Figure 0007630559000001
    Figure 0007630559000001
Patent Text Reader

Abstract

To provide a positive electrode active material including a lithium nickel-containing composite oxide coated with a compound containing W and Li, having excellent battery characteristic without marring the crystallinity, where a fine particle and / or coating of the compound containing W and Li is present on a surface of a primary particle.SOLUTION: A method for manufacturing a positive electrode active material for a lithium ion secondary battery comprises the step of preparing a lithium nickel-containing composite oxide by mixing a nickel compound and a lithium compound into a lithium-mixed material and then, increasing the temperature of the lithium-mixed material from a room temperature to a baking temperature equal to or higher than 700°C under an oxidizing atmosphere. In the preparing step, a filtrate obtained by putting, in 1 L of deionized water, 1.25 kg of a lithium nickel-containing composite oxide obtained under the condition of the passing time and / or holding time being set to be 45 minutes or a shorter time in a temperature region where the temperature of the lithium-mixed material is 600-650°C, followed by stirring and filtering the resultant mixture has an electric conductivity in a range of 42.5 mS / cm to 62.5 mS / cm. The lithium nickel-containing composite oxide is used as a base material to form a fine particle and / or coating of a compound containing W and Li on the surface of its primary particle.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium-nickel-containing composite oxide coated with a compound containing W and Li to be used as a positive electrode active material for lithium ion secondary batteries, more specifically to a lithium-nickel-containing composite oxide that serves as a base material for a positive electrode active material for lithium ion secondary batteries, the lithium-nickel-containing composite oxide being coated with a compound containing W and Li, in which fine particles and / or a coating of a compound containing W and Li, such as lithium tungstate, are present on the surfaces of the primary particles.

[0002] The present invention also relates to a positive electrode active material for lithium ion secondary batteries using the lithium nickel-containing composite oxide as a base material, and a method for producing the same. [Background technology]

[0003] In recent years, with the widespread use of small information terminals such as smartphones and tablet PCs, there is a strong demand for the development of small, lightweight secondary batteries with high energy density, as well as large, high-output secondary batteries for use in hybrid and electric vehicles.

[0004] Lithium ion secondary batteries are a type of secondary battery that meets these requirements. Lithium ion secondary batteries are composed of a negative electrode, a positive electrode, a separator, and a non-aqueous electrolyte, and the active materials that compose the negative electrode and positive electrode are materials that can extract and insert lithium during charging and discharging. As the non-aqueous electrolyte, a non-aqueous electrolyte solution obtained by dissolving a lithium salt, which is a supporting salt, in an organic solvent, or a solid electrolyte that is non-flammable and ionically conductive is used.

[0005] Research and development of lithium-ion secondary batteries is still being actively conducted. Lithium-ion secondary batteries that use lithium transition metal-containing composite oxides with a layered rock-salt or spinel structure as the positive electrode active material can achieve a high voltage of about 4 V, and are therefore being put into practical use as secondary batteries with high energy density.

[0006] The main lithium transition metal-containing composite oxides that have been proposed so far are lithium cobalt composite oxide (LiCoO2), which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2), which uses nickel, which is cheaper than cobalt, and lithium nickel cobalt manganese composite oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples of suitable oxides include lithium manganese composite oxides (LiMn2O4) that use manganese, and lithium transition metal-containing composite oxides to which additive elements are added depending on the characteristics required.

[0007] Of these, lithium nickel composite oxide has the advantage that it has a larger charge / discharge capacity per weight than lithium cobalt composite oxide, and that its main raw material, nickel, is cheaper and more readily available than cobalt. For these reasons, it is expected to become the next-generation positive electrode active material, and research and development into it is currently being actively carried out.

[0008] Lithium nickel composite oxides are usually produced by mixing and sintering a lithium compound and a nickel compound, and are composed of a powder of monodispersed primary particles or a powder of secondary particles that are aggregates of primary particles. However, both have the disadvantage that their thermal stability in a charged state is inferior to that of lithium cobalt composite oxides.

[0009] In response to this, in order to stabilize the crystal structure when lithium is removed during charging and to obtain a lithium-nickel composite oxide that has good thermal stability and charge-discharge cycle characteristics as a positive electrode active material, it is common to replace a portion of the nickel in the lithium-nickel composite oxide with another substance.

[0010] However, in a lithium-nickel-containing composite oxide in which a part of the nickel in the lithium-nickel composite oxide is replaced with another substance to reduce the nickel ratio, the thermal stability is increased, but the battery capacity is reduced. On the other hand, if the nickel ratio in the lithium-nickel-containing composite oxide is increased in order to prevent the reduction in the battery capacity, the thermal stability is not sufficiently improved. Moreover, if the nickel ratio in the lithium-nickel-containing composite oxide is increased, there is a problem that cation mixing is likely to occur during firing, making synthesis difficult.

[0011] On the other hand, for lithium ion secondary batteries, there is a strong demand for higher output (lower resistance), particularly in battery applications for hybrid vehicles and electric vehicles. In response to such demands, a method of adding a tungsten compound to a lithium nickel-containing composite oxide has been investigated in order to improve the output characteristics of the positive electrode active material.

[0012] For example, JP 2012-079464 A describes a compound of the general formula Li z Ni 1-x-y Co x M y There has been proposed a positive electrode active material for non-aqueous electrolyte secondary batteries, which comprises a lithium-nickel-containing composite oxide coated with a compound containing W and Li, the lithium-nickel-containing composite oxide comprising a base material of primary particles represented by the formula O2 (where 0.10≦x≦0.35, 0≦y≦0.35, 0.97≦z≦1.20, and M is at least one element selected from Mn, V, Mg, Mo, Nb, Ti, and Al) and secondary particles formed by agglomeration of the primary particles, and having fine particles of a compound containing W and Li, in particular fine particles made of lithium tungstate, on the surfaces of the primary particles.

[0013] By having fine particles and / or coatings of compounds containing W and Li, such as lithium tungstate, present on the surface of the primary particles that make up the lithium-nickel-containing composite oxide base material, these fine particles or coatings prevent contact between the lithium-nickel-containing composite oxide and the electrolyte and function as a protective film that suppresses the formation of deposits such as phosphates.In addition, because these fine particles or coatings have a crystal structure that has a Li diffusion path, it is believed that interfacial resistance can be reduced.

[0014] However, although this positive electrode active material has improved output characteristics, it is insufficient in terms of increasing capacity due to the low nickel ratio, and if the nickel ratio is increased, thermal stability must also be considered. For this reason, research has been conducted on lithium nickel-containing composite oxides coated with compounds containing W and Li, in which fine particles and / or coatings of compounds containing W and Li, such as lithium tungstate, are present on the surfaces of the primary particles, which achieve both high capacity and high output as a positive electrode active material and are also excellent in thermal stability.

[0015] For example, in JP 2015-216105 A, a lithium mixture obtained by mixing a nickel compound and a lithium compound is fired in an oxidizing atmosphere at a temperature range of 700° C. to 780° C. for 1 hour to 6 hours to obtain a lithium mixture having the general formula: Li b Ni 1―x―y Co x M yO2 (wherein M represents at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, and Mo; 0.95 ≦ b ≦ 1.03, 0 < x ≦ 0.15, 0 < y ≦ 0.07, x + y ≦ 0.16), obtained using a lithium nickel-containing composite oxide composed of primary particles and secondary particles formed by aggregation of the primary particles as a base material, adding a tungsten compound during or after the water washing treatment of the base material to disperse W on the surface of the primary particles of the base material, and heat-treating at a temperature of 100°C to 600°C in an oxygen atmosphere or a vacuum atmosphere, having fine particles of a compound containing W and Li on the surface of the primary particles of the base material, and further, the lithium nickel-containing composite oxide of the base material has a lattice constant length in the c-axis direction obtained from the Rietveld analysis of X-ray diffraction of 14.183 Å or more. A positive electrode active material for a non-aqueous electrolyte secondary battery has been proposed.

[0016] Further, in JP-A-2017-084513, a tungsten compound is added during or after the water washing treatment of a base material obtained in the same manner as in JP-A-2015-216105, and in a state where the moisture content of the base material is controlled to 6.5 mass% to 11.5 mass%, W is dispersed on the surface of the primary particles of the base material, and obtained by heat-treating at a temperature of 100°C to 600°C in an oxygen atmosphere or a vacuum atmosphere, having a film with a thickness of 1 nm to 200 nm containing W and Li on the surface of the primary particles of the base material, and further, the lithium nickel-containing composite oxide of the base material has a lattice constant length in the c-axis direction obtained from the Rietveld analysis of X-ray diffraction of 14.183 Å to 14.205 Å. A positive electrode active material for a non-aqueous electrolyte secondary battery has been proposed.

[0017] In these documents, in order to remove crystal water and the like in the lithium compound and uniformly react the lithium compound and the nickel compound in the temperature range where crystal growth of the lithium nickel-containing composite oxide serving as the base material proceeds, it is described that it is preferable to perform firing in two steps at a temperature of 400°C to 600°C for 1 hour to 5 hours and then at a temperature of 700°C to 780°C for 3 hours or more.

Prior Art Documents

Patent Documents

[0018] [Patent Document 1] JP 2012-079464 A [Patent Document 2] JP 2015-216105 A [Patent Document 3] JP 2017-084513 A Summary of the Invention [Problem to be solved by the invention]

[0019] In the technologies disclosed in JP 2015-216105 A and JP 2017-084513 A, a lithium-nickel-containing composite oxide coated with a compound containing W and Li, such as lithium tungstate, is formed by having fine particles and / or a coating of a compound containing W and Li present on the surface of the primary particles. By having fine particles and / or a coating of a compound containing W and Li present on the surface of the primary particles of the lithium-nickel-containing composite oxide, the insertion and extraction of lithium is improved, reaction resistance is reduced, and high capacity and high output are achieved. In addition, crystallinity is improved, achieving high thermal stability even with a high nickel ratio.

[0020] However, for battery applications in hybrid and electric vehicles, there is a demand for lithium ion secondary batteries to achieve even higher levels of capacity and power output.

[0021] In view of the above problems, the present invention aims to improve the battery characteristics, particularly the discharge capacity and charge / discharge characteristics, of a lithium-ion secondary battery using a lithium-nickel-containing composite oxide coated with a compound containing W and Li, which has fine particles and / or a coating of a compound containing W and Li, such as lithium tungstate, present on its surface. [Means for solving the problem]

[0022] In order to solve the above problems, the inventors focused on the lithium nickel-containing composite oxide itself, which is the base material of a lithium nickel-containing composite oxide coated with a compound containing W and Li, in which fine particles and / or a coating of a compound containing W and Li, such as lithium tungstate, are present on the surfaces of the primary particles, and conducted extensive research into the properties of the lithium nickel-containing composite oxide suitable for causing fine particles and / or a coating of a compound containing W and Li to be present on the surfaces of the primary particles, as well as the production conditions for obtaining a lithium nickel-containing composite oxide having such properties.

[0023] As a result, it was found that by appropriately controlling the temperature holding time within a specific temperature range in the firing step for producing the lithium nickel-containing composite oxide, it is possible to appropriately control the amount of lithium compound corresponding to excess Li present on the surface of the primary particles of the obtained lithium nickel-containing composite oxide. In this way, it was found that by controlling the amount of excess Li present on the surface of the primary particles within a predetermined range, it is possible to obtain a lithium nickel-containing composite oxide in which fine particles and / or coatings of compounds containing W and Li, such as lithium tungstate, which have excellent battery properties, are present on the surface of the primary particles by reacting the lithium compound with the tungsten compound without extracting Li from the crystals.

[0024] The present invention was completed based on these findings.

[0025] A first aspect of the present invention relates to a lithium-nickel-containing composite oxide that is a base material for a positive electrode active material for a lithium-ion secondary battery, the lithium-nickel-containing composite oxide being composed of primary particles and / or secondary particles formed by aggregation of the primary particles, with fine particles and / or coatings of a compound containing W and Li present on the surfaces of the primary particles.

[0026] The lithium nickel-containing composite oxide of the present invention is characterized in that the filtrate obtained by adding 1.25 kg of the lithium nickel-containing composite oxide to 1 L of pure water, stirring, and filtering has an electrical conductivity in the range of 42.5 mS / cm to 62.5 mS / cm. 。

[0027] Applicable The lithium nickel-containing composite oxide is General formula: Li a Ni 1-x―y Co x M y O2···(1) (In the formula, M is at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo, and W; 0.98≦a≦1.11, 0 <x≦0.15、0<y≦0.07、および、x+y≦0.16である。) It is preferable that the composition of the composition is:

[0028] The length of the lattice constant in the c-axis direction of the crystal of the lithium-nickel-containing composite oxide obtained by Rietveld analysis of X-ray diffraction is preferably in the range of 14.183 Å to 14.205 Å.

[0029] The volume-based average particle size MV of the lithium nickel-containing composite oxide is preferably in the range of 5 μm to 30 μm.

[0030] A second aspect of the present invention relates to a method for producing a positive electrode active material for a lithium ion secondary battery, i.e., a lithium-nickel-containing composite oxide coated with a compound containing W and Li, which comprises primary particles and / or secondary particles formed by aggregation of the primary particles, and in which fine particles and / or coatings of a compound containing W and Li are present on the surfaces of the primary particles.

[0031] The method for producing a positive electrode active material for a lithium ion secondary battery of the present invention comprises the steps of: The lithium nickel-containing composite oxide according to the first aspect of the present invention In a step of preparing a lithium mixture by mixing a nickel compound and a lithium compound to obtain the lithium mixture, and then heating the lithium mixture in an oxidizing atmosphere from room temperature to a firing temperature of 700°C or more, the time for passing and / or holding the lithium mixture in a temperature range of 600°C to 650°C is set to 20 minutes or more and 45 minutes or less; The lithium nickel-containing composite oxide is used as a base material.A slurry is formed using the lithium nickel-containing composite oxide so that the amount of the lithium nickel-containing composite oxide is 700 g to 2000 g per 1 L of water, and the lithium nickel-containing composite oxide is washed with water. During or after the water washing treatment, a tungsten compound is added to the lithium nickel-containing composite oxide to disperse W on the surfaces of the primary particles of the lithium nickel-containing composite oxide; and The lithium nickel-containing composite oxide having W dispersed on the surfaces of the primary particles is heat-treated to form fine particles and / or a coating of a compound containing W and Li on the surfaces of the primary particles of the lithium nickel-containing composite oxide. It is characterized by:

[0032] The positive electrode active material for a lithium ion secondary battery is General formula: Li a Ni 1―x―y Co x M y W z O 2+α ···(2) (In the formula, M is at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo, and W. 0.95≦a≦1.10, 0 <x≦0.15、0<y≦0.07、x+y≦0.16、0.001≦z≦0.03、0≦α≦0.2である。) It is preferable that the lithium-nickel-containing composite oxide is coated with a compound containing W and Li, and has a composition consisting of the above.

[0033] The amount of W dispersed on the surfaces of the primary particles of the lithium nickel-containing composite oxide is preferably in the range of 0.1 atomic % to 3.0 atomic % relative to the total number of Ni, Co and M atoms contained in the lithium nickel-containing composite oxide.

[0034] The heat treatment is preferably carried out at a temperature in the range of 100° C. to 600° C. in an oxygen atmosphere or a vacuum atmosphere.

[0035] A third aspect of the present invention relates to a positive electrode active material for a lithium ion secondary battery, i.e., a lithium-nickel-containing composite oxide coated with a compound containing W and Li, which comprises primary particles and / or secondary particles formed by aggregation of the primary particles, and in which fine particles and / or coatings of a compound containing W and Li are present on the surfaces of the primary particles.

[0036] The positive electrode active material for a lithium ion secondary battery of the present invention is characterized in that the lithium nickel-containing composite oxide according to the first aspect of the present invention, i.e., the lithium nickel-containing composite oxide obtained by adding 1.25 kg of the lithium nickel-containing composite oxide to 1 L of pure water, stirring, and filtering the resulting filtrate has an electrical conductivity in the range of 42.5 mS / cm to 62.5 mS / cm, is used as a base material, and fine particles and / or a coating of a compound containing W and Li are present on the surfaces of the primary particles.

[0037] The positive electrode active material for a lithium ion secondary battery is General formula: Li a Ni 1―x―y Co x M y W z O 2+α (2) (In the formula, M is at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo, and W. 0.95≦a≦1.10, 0 <x≦0.15、0<y≦0.07、x+y≦0.16、0.001≦z≦0.03、0≦α≦0.2である。) It is preferable that the lithium-nickel-containing composite oxide is coated with a compound containing W and Li, and has a composition consisting of the above.

[0038] The lattice constant length in the c-axis direction of the crystal of the lithium-nickel-containing composite oxide coated with the compound containing W and Li, obtained from Rietveld analysis of X-ray diffraction, is preferably in the range of 14.183 Å to 14.205 Å.

[0039] The volume-based average particle size MV of the lithium-nickel-containing composite oxide coated with the compound containing W and Li is preferably in the range of 5 μm to 30 μm. Effect of the Invention

[0040] According to the present invention, in a lithium nickel-containing composite oxide, which is a base material of a lithium nickel-containing composite oxide coated with a compound containing W and Li, in which fine particles and / or a coating of a compound containing W and Li, such as lithium tungstate, are present on the surface of the primary particles, the amount of unreacted lithium compound, i.e., excess lithium compound, present on the surface of the primary particles can be appropriately regulated. Therefore, when fine particles and / or a coating of a compound containing W and Li are formed on the surface of the primary particles of the lithium nickel-containing composite oxide, extraction of Li from the crystals is prevented. Therefore, it is possible to provide a positive electrode active material for a lithium ion secondary battery having excellent battery characteristics without impairing the crystallinity. [Brief description of the drawings]

[0041] [Figure 1] FIG. 1 is a perspective view and a cross-sectional view showing a 2032 type coin battery used in the battery evaluation. [Diagram 2] FIG. 2 is a schematic explanatory diagram of an equivalent circuit used for impedance measurement and analysis in battery evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0042] As mentioned above, the present inventors ,TaThe present inventors focused on the lithium nickel-containing composite oxide itself, which is the base material for a positive electrode active material for lithium ion secondary batteries, and which is made of a lithium nickel-containing composite oxide coated with a compound containing W and Li, in which fine particles and / or a coating of a compound containing W and Li, such as lithium ungstate, are present on the surfaces of the primary particles. They have conducted extensive research into the properties of the lithium nickel-containing composite oxide that are suitable for causing fine particles and / or a coating of a compound containing W and Li to be present on the surfaces of the primary particles, as well as the production conditions for obtaining a lithium nickel-containing composite oxide having such properties. As a result, it was found that by appropriately controlling the temperature retention time within a specific temperature range in the firing step for producing the lithium nickel-containing composite oxide, the amount of lithium compound present on the surface of the primary particles of the obtained lithium nickel-containing composite oxide and corresponding to excess Li can be appropriately controlled, and thus, when forming fine particles and / or a coating of a compound containing W and Li on the surface of the primary particles of the lithium nickel-containing composite oxide, extraction of Li from the crystals can be prevented, and a positive electrode active material for a lithium ion secondary battery having excellent battery characteristics can be obtained, and that whether the amount of excess Li in the lithium nickel-containing composite oxide used as the base material is appropriate can be easily confirmed by putting 1.25 kg of the lithium nickel-containing composite oxide into 1 L of pure water, stirring, and filtering the resulting filtrate, and checking whether the electrical conductivity of the filtrate is in the range of 42.5 mS / cm to 62.5 mS / cm. The present invention was completed based on such findings.

[0043] Each aspect of the present invention will be described in detail below.

[0044] 1. Lithium nickel-containing composite oxide A first aspect of the present invention relates to a lithium-nickel-containing composite oxide, which is a base material of a lithium-nickel-containing composite oxide coated with a compound containing W and Li, in which fine particles and / or a coating of a compound containing W and Li, such as lithium tungstate, are present on the surfaces of primary particles.

[0045] The lithium nickel-containing composite oxide of the present invention comprises primary particles and agglomerates of the primary particles. collection The lithium nickel-containing composite oxide is composed of secondary particles formed by adding 1.25 kg of the lithium nickel-containing composite oxide to 1 L of pure water, stirring, and filtering the resulting filtrate, which has an electrical conductivity in the range of 42.5 mS / cm to 62.5 mS / cm.

[0046] [Conductivity of filtrate] Usually, in the finally obtained positive electrode active material for lithium ion secondary batteries, the amount of excess Li, i.e., the amount of Li dissolved in water, is reduced, for example, to 0.2 mass% or less relative to the entire lithium nickel-containing composite oxide. However, as described above, the inventors have focused on the reaction between Li of the lithium nickel-containing composite oxide and W of a tungsten compound when forming fine particles and / or a coating of a compound containing W and Li on the surface of the primary particles of the lithium nickel-containing composite oxide as the base material of the positive electrode active material for lithium ion secondary batteries, and have found that by appropriately controlling the amount of excess Li in the lithium nickel-containing composite oxide as the base material, it is possible to form suitable fine particles and / or a coating of a compound containing W and Li without extracting Li present inside the primary particles of the lithium nickel-containing composite oxide in the reaction between Li of the lithium nickel-containing composite oxide and W of the tungsten compound.

[0047] In the present invention, the amount of surplus Li in the lithium-nickel-containing composite oxide that is the base material of the positive electrode active material for lithium-ion secondary batteries can be measured as the electrical conductivity of the filtrate obtained by adding 1.25 kg of the lithium-nickel-containing composite oxide to 1 L of pure water, stirring, and filtering.

[0048] If the conductivity of the filtrate is less than 42.5 mS / cm, the excess Li present on the surfaces of the primary particles of the lithium-nickel-containing composite oxide is insufficient, and Li is extracted from the crystals during the reaction between Li of the lithium-nickel-containing composite oxide and W of the tungsten compound.

[0049] When the conductivity of the filtrate is 42.5 mS / cm or more, a lithium ion secondary battery using the finally obtained positive electrode active material for lithium ion secondary batteries can achieve sufficient discharge capacity and charge / discharge efficiency.

[0050] On the other hand, if the conductivity of the filtrate exceeds 62.5 mS / cm, the amount of surplus Li present on the surface of the primary particles of the lithium-nickel-containing composite oxide becomes excessive, and in the finally obtained positive electrode active material for a lithium-ion secondary battery, the Li site occupancy rate decreases, the crystallinity deteriorates, and the battery characteristics deteriorate.

[0051] The conductivity of the filtrate is preferably in the range of 45 mS / cm to 60 mS / cm, and more preferably 50 mS / cm to 60 mS / cm.

[0052] The conductivity of the filtrate is measured using a conductivity meter for the filtrate obtained by adding 1.25 kg of the lithium-nickel-containing composite oxide to 1 L of pure water, i.e., adding 125 parts by mass of the lithium-nickel-containing composite oxide to 100 parts by mass of pure water, stirring, and filtering.

[0053] A stirrer or other stirrer can be used for stirring, and any means such as natural filtration, reduced pressure filtration, pressure filtration, centrifugal filtration, etc. can be used for filtration.

[0054] The lithium nickel-containing composite oxide of the present invention is a base material for a positive electrode active material for a lithium ion secondary battery, i.e., a base material for forming fine particles of a compound containing W and Li, or a coating composed of a compound containing W and Li, on the surface of its primary particles, and such particle properties consisting of primary particles and / or secondary particles formed by aggregation of primary particles can be obtained by the production method described in the first aspect of the present invention.

[0055] [composition] The lithium nickel-containing composite oxide of the present invention is General formula: Li a Ni 1-x―y Cox M y O2···(1) (In the formula, M is at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo, and W, 0.98 ≦ a ≦ 1.11, 0 < x ≦ 0.15, 0 < y ≦ 0.07, and x + y ≦ 0.16.) Preferably, it has a composition consisting of

[0056] The lithium nickel-containing composite oxide of the present invention is a hexagonal layered compound. In the above general formula, (1 - x - y) indicating the Ni content is 0.84 or more and less than 1.

[0057] In the lithium nickel-containing composite oxide of the present invention, the higher the Ni content, the higher the capacity can be achieved when the finally obtained positive electrode active material is used. However, if the Ni content is too high, sufficient thermal stability cannot be obtained, and cation mixing is likely to occur during firing. On the other hand, when the Ni content decreases, problems such as a decrease in capacity and an inability to sufficiently obtain the capacity per battery volume even when the packing density of the positive electrode is increased also occur.

[0058] Therefore, the Ni content of the lithium nickel-containing composite oxide is preferably 0.84 or more and 0.98 or less, more preferably 0.845 or more and 0.950 or less, and even more preferably 0.85 or more and 0.95 or less.

[0059] x indicating the Co content is 0 < x ≦ 0.15, preferably 0.02 ≦ x ≦ 0.15, and more preferably 0.03 ≦ x ≦ 0.13.

[0060] When the Co content is within the above range, excellent cycle characteristics and thermal stability can be obtained in the finally obtained positive electrode active material. By increasing the Co content, the cycle characteristics of the positive electrode active material can be improved. However, when the Co content exceeds 0.15, it becomes difficult to increase the capacity of the positive electrode active material.

[0061] y, which represents the content of at least one element M selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo, and W, satisfies 0 < y ≤ 0.07, and preferably 0.01 ≤ y ≤ 0.05. When the content of M is within the above range, excellent cycle characteristics and thermal stability can be obtained.

[0062] When y exceeds 0.07, it becomes difficult to increase the capacity of the positive electrode active material. If the additive element M is not added, the effect of improving the battery characteristics cannot be obtained. Therefore, in order to sufficiently obtain the effect of improving the battery characteristics, it is preferable that y is 0.01 or more.

[0063] Note that M contains at least Al, and in the finally obtained lithium nickel-containing composite oxide, it is preferable that y, which represents the content of Al, is 0.03 to 0.07.

[0064] a, which represents the Li content, satisfies 0.95 ≤ a ≤ 1.03. When a is less than 0.95, metal elements such as Ni are mixed into the Li layer in the layered compound, resulting in a decrease in the Li insertion / extraction property. Therefore, as the Li site occupancy rate decreases, the battery capacity decreases and the output characteristics deteriorate. On the other hand, when a exceeds 1.03, Li is mixed into the metal layer in the layered compound, resulting in a decrease in the battery capacity.

[0065] Therefore, in order to make the Li content in the lithium nickel-containing composite oxide good in terms of battery capacity and output characteristics, 0.95 ≤ a ≤ 1.03, and more preferably 0.95 ≤ a ≤ 1.01.

[0066] [Length of the lattice constant in the c-axis direction] Here, the Ni content in the lithium nickel-containing composite oxide of the present invention is 0.84 or more, preferably 0.98 or less, and has a very high Ni content. When the Ni content increases, problems such as a decrease in thermal stability occur. Therefore, usually, the Ni content is lower than 0.84 and is generally adjusted to be about 0.80 to 0.83.

[0067] However, in the present invention, a high nickel content is made possible by appropriately controlling the length of the lattice constant in the c-axis direction (hereinafter referred to as the "c-axis length") obtained by performing Rietveld analysis of X-ray diffraction on the crystals of the lithium-nickel-containing composite oxide.

[0068] That is, a high nickel ratio is made possible by making the length of the c-axis of the crystal of the lithium nickel-containing composite oxide 14.183 Å or more, preferably 14.185 Å or more.

[0069] In the case of the hexagonal lithium-nickel-containing composite oxide of the present invention, the length of the c-axis affects the insertion and extraction of Li from the crystal. In general, as the length of the c-axis increases, the interlayer distance of the lithium layers increases, improving the insertion and extraction of Li from the crystal. By using such a lithium-nickel-containing composite oxide as a base material, a positive electrode active material with high capacity and high output can be obtained.

[0070] On the other hand, when the c-axis length is shorter than 14.183 Å, the insertion and extraction of Li from the crystal is reduced, resulting in a decrease in the capacity and output of the final positive electrode active material. In addition, the crystallinity is reduced due to cation mixing, which deteriorates the cycle characteristics and thermal stability.

[0071] The upper limit of the length of the c-axis is not particularly limited, but the upper limit is about 14.205 Å, and in the present invention, the length of the c-axis is preferably in the range of 14.183 Å to 14.205 Å.

[0072] [Average particle size] The volume-based average particle size MV of the particles (primary particles and / or secondary particles) constituting the lithium-nickel-containing composite oxide of the present invention is preferably in the range of 5 μm to 30 μm, more preferably in the range of 5 μm to 25 μm, even more preferably in the range of 8 μm to 20 μm, and even more preferably in the range of 8 μm to 17 μm.

[0073] If the volume-based average particle size MV is less than 5 μm, the packing property in the positive electrode when used as a positive electrode active material of a battery may decrease, and the battery capacity per volume may decrease. On the other hand, if the volume-based average particle size MV exceeds 30 μm, the contact area between the positive electrode active material and the electrolyte of the battery may decrease, and the battery capacity and output characteristics may decrease.

[0074] Therefore, by controlling the volume-based average particle diameter MV within the above-mentioned range, the finally obtained positive electrode active material can further improve the filling property in the positive electrode while maintaining the battery capacity and output characteristics. In addition, the finally obtained positive electrode active material is composed of primary particles and / or secondary particles, and due to such a particle structure, contact with the electrolyte occurs not only on the outer surface of the secondary particles, but also in the vicinity of the surface of the secondary particles, in the internal voids, and even incomplete grain boundaries. From the viewpoint of sufficient contact with the electrolyte, it is preferable to set the volume-based average particle diameter MV to the above-mentioned range.

[0075] The specific surface area of ​​the lithium nickel-containing composite oxide of the present invention measured by the BET method is 0.20 m 2 / g~0.50m 2 / g, and preferably in the range of 0.25m 2 / g~0.45m 2 It is more preferable that the range is / g.

[0076] By having such a specific surface area, the contact with the electrolyte is in an appropriate range, and the battery capacity and output characteristics can be improved. 2 When the BET specific surface area is less than 0.50 m / g, the amount of excess Li present on the surface of the primary particles of the lithium nickel-containing composite oxide is insufficient, and Li is extracted from the crystals during the reaction between Li of the lithium nickel-containing composite oxide and W of the tungsten compound. 2When the Li content exceeds 1 / g, the amount of surplus Li present on the surface of the primary particles of the lithium nickel-containing composite oxide becomes excessive, that is, the reaction between the nickel compound and the lithium compound does not proceed sufficiently in the synthesis of the lithium nickel-containing composite oxide, and therefore, in the finally obtained positive electrode active material for lithium ion secondary batteries, the Li site occupancy rate decreases, the crystallinity deteriorates, and the battery characteristics deteriorate.

[0077] [Method of manufacturing lithium nickel-containing composite oxide] The lithium nickel-containing composite oxide according to the first embodiment of the present invention can be obtained by the following production method. Specifically, in the step of preparing a lithium mixture by mixing a nickel compound and a lithium compound, and then heating the lithium mixture in an oxidizing atmosphere from room temperature to a firing temperature of 700°C or higher to prepare a lithium nickel-containing composite oxide composed of primary particles and / or secondary particles formed by aggregation of the primary particles, the time for passing and / or the time for holding the lithium mixture in a temperature range of 600°C to 650°C are: More than 20 minutes 45 minutes or less, preferably 20 The range is from 1 to 40 minutes.

[0078] (Nickel compounds) The nickel compound used in the firing step is a compound containing Ni and Co, and containing at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo and W as an additional element M.

[0079] As the nickel compound, for example, any of nickel composite hydroxides, nickel oxycomposite hydroxides obtained by oxidizing the nickel composite hydroxide with an oxidizing agent, and nickel composite oxides obtained by oxidative roasting the nickel composite hydroxide and / or the nickel oxycomposite hydroxide at a temperature in the range of 500°C to 750°C can be used.

[0080] The nickel composite hydroxide is not limited to these, but nickel composite hydroxides obtained by crystallization methods such as coprecipitation and homogeneous precipitation can be used.

[0081] In the crystallization method, nickel composite hydroxide can be obtained under various conditions, and the crystallization conditions are not particularly limited, but those obtained under the following conditions are preferable.

[0082] Specifically, a nickel composite hydroxide is preferred, which is obtained by dropping an aqueous solution of a metal compound containing Ni and Co and containing at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo, and W as an added element M, and an aqueous solution containing an ammonium ion donor into a reaction tank heated to a temperature in the range of 40°C to 60°C.

[0083] During crystallization, it is preferable to dropwise add an aqueous solution of an alkali metal hydroxide as necessary so that the reaction solution can be kept alkaline, preferably in a range of pH 10 to 14 at a liquid temperature of 25°C.

[0084] Furthermore, a nickel composite hydroxide that contains Ni and Co and also contains the additive element M can be obtained by coprecipitating the additive element M with Ni and Co, or by obtaining a nickel composite hydroxide by crystallization, and then coating the nickel composite hydroxide with a metal compound containing the additive element M, or by impregnating the nickel composite hydroxide with an aqueous solution containing the metal compound of the additive element M.

[0085] The nickel composite hydroxide obtained by such a crystallization method is composed of a powder with a high bulk density. Since such a composite hydroxide with a high bulk density is likely to produce a lithium-nickel-containing composite oxide having a small specific surface area and consisting of primary particles and / or secondary particles formed by agglomeration of the primary particles after the water washing treatment following the firing step, the nickel composite hydroxide is suitable as a raw material for a positive electrode active material for a lithium ion secondary battery.

[0086] When nickel hydroxide is crystallized at a temperature of more than 60°C or a pH of more than 14, the priority of nucleation in the solution increases, and crystal growth does not proceed, so that only fine particles may be obtained. On the other hand, when nickel composite hydroxide is crystallized at a temperature of less than 40°C or a pH of less than 10, nucleation in the solution is low, and crystal growth of particles takes precedence, so that coarse particles may be mixed into the obtained nickel composite hydroxide. In addition, the amount of metal ions remaining in the reaction solution increases, and composition deviation may occur. When nickel composite hydroxide with such coarse particles mixed in or composition deviation is used as a raw material, the battery characteristics of the obtained positive electrode active material are deteriorated.

[0087] Therefore, when a nickel composite hydroxide obtained by a crystallization method is used as the nickel compound, it is preferable to perform crystallization of the nickel composite hydroxide while maintaining the reaction solution at a temperature in the range of 40°C to 60°C and maintaining the reaction solution at a pH value of 10 to 14 based on a liquid temperature of 25°C.

[0088] When a nickel composite oxyhydroxide is used as the nickel compound, the method for producing it is not particularly limited. However, when the nickel composite hydroxide is prepared by oxidizing it with an oxidizing agent such as sodium hypochlorite or hydrogen peroxide solution, particles with a high bulk density can be obtained, so it is preferable to use the nickel composite oxyhydroxide obtained by this method.

[0089] When a nickel composite oxide is used as the nickel compound, the method for producing it is not particularly limited, but it is preferable to obtain the nickel composite hydroxide and / or nickel composite oxyhydroxide by oxidative roasting in an oxidative atmosphere at a temperature in the range of 500°C to 750°C, and the oxidative roasting temperature is more preferably in the range of 550°C to 700°C.

[0090] By using the nickel composite oxide thus obtained, it is possible to stabilize the composition ratio of Li to metals other than Li in the lithium nickel-containing composite oxide when the lithium mixture obtained by mixing it with a lithium compound is calcined to obtain the lithium nickel-containing composite oxide. This provides the advantage that when a positive electrode active material using the lithium nickel-containing composite oxide as a base material is used in a lithium ion secondary battery, it is possible to achieve high capacity and high output.

[0091] When the nickel composite hydroxide and / or nickel composite oxyhydroxide is oxidatively roasted at an oxidative roasting temperature of less than 500°C, the conversion to the oxide may be incomplete. If such a nickel composite oxide incompletely converted to the oxide is used, it becomes difficult to stabilize the composition of the resulting lithium-nickel-containing composite oxide, and the composition is likely to become non-uniform during firing. In addition, nickel composite hydroxide and / or nickel composite oxyhydroxide may remain in the nickel composite oxide after oxidative roasting, which may cause steam generation during firing, inhibiting the reaction between the lithium compound and the nickel composite oxide and reducing the crystallinity.

[0092] On the other hand, if the oxidizing roasting temperature exceeds 750°C, the crystallinity of the resulting nickel composite oxide will be high, and the reactivity of the lithium compound and the nickel composite oxide in the subsequent firing step will decrease, which may result in a decrease in the crystallinity of the finally obtained lithium-nickel-containing composite oxide. Alternatively, the nickel composite oxide may undergo rapid grain growth, forming a nickel composite oxide made of coarse particles, which may result in the average particle size of the finally obtained lithium-nickel-containing composite oxide becoming too large.

[0093] The retention time at the oxidizing roasting temperature is preferably set in the range of 1 to 10 hours, and more preferably in the range of 2 to 6 hours. If it is less than 1 hour, the conversion to the oxide may be incomplete, and if it exceeds 10 hours, the crystallinity of the nickel composite oxide may become too high.

[0094] The atmosphere for the oxidizing roasting may be any oxidizing atmosphere, but in consideration of handling and cost, it is preferable to use an air atmosphere.

[0095] The nickel composite hydroxide used as the nickel compound preferably has a sulfate (SO4) content in the range of 0.1% to 0.4% by mass, more preferably 0.1% to 0.3% by mass, which makes it easier to control the crystallinity of the lithium-nickel-containing composite oxide in the subsequent firing step.

[0096] In the case of obtaining a nickel composite hydroxide by a crystallization method and using a sulfate such as nickel sulfate as a raw material, it is possible to regulate the content of sulfate radicals to a range of 0.1% by mass to 0.4% by mass by thoroughly washing the nickel composite hydroxide with an alkaline aqueous solution adjusted to a pH of 11 to 13 at a liquid temperature of 25°C.

[0097] In addition, by using a nickel compound containing Ni, Co, and at least one additive element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo and W as the nickel compound, the lithium nickel-containing composite oxide of the first aspect, i.e., General formula: Li a Ni 1-x―y Co x M y O2···(1) (In the formula, M is at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo, and W; 0.98≦a≦1.11, 0 <x≦0.15、0<y≦0.07、および、x+y≦0.16である。) It is preferable to obtain a lithium nickel-containing composite oxide having a composition consisting of:

[0098] (mixed with lithium compounds) The lithium compound to be mixed with the nickel compound is not particularly limited, but it is preferable to use at least one selected from the group consisting of hydroxides, oxyhydroxides, oxides, carbonates, nitrates, and halides of lithium. By using these, it is possible to obtain an advantage that no impurities remain after firing. Among these, it is more preferable to use lithium hydroxide, which has good reactivity with the nickel compound.

[0099] The mixing ratio of the nickel compound and the lithium compound is not particularly limited, but the composition of Li and metal elements other than Li in the lithium nickel-containing composite oxide after firing is almost maintained in the composition in the mixture obtained by mixing the nickel compound and the lithium compound. Therefore, it is preferable to adjust the amount of Li in the lithium compound to 0.98 to 1.11 in molar ratio with respect to the total amount of Ni, Co, and other additive elements M in the nickel compound. If this molar ratio is less than 0.98, the crystallinity of the obtained fired powder may be very poor. In addition, the lithium content in the obtained fired powder may be less than 0.98. On the other hand, if this molar ratio exceeds 1.11, firing is likely to proceed and over-firing is likely to occur, and the Li content of the obtained fired powder may also exceed 1.11.

[0100] The device and method for mixing the nickel compound and the lithium compound are not particularly limited as long as they can be mixed uniformly. For example, a dry mixer such as a V blender or a mixing granulator can be used.

[0101] (Firing) The lithium mixture obtained by mixing the nickel compound and the lithium compound is fired at a firing temperature of 700° C. or higher in an oxidizing atmosphere.

[0102] A lithium-nickel-containing composite oxide is produced when the material is fired at a temperature exceeding 500° C., but the crystals are underdeveloped and structurally unstable at temperatures below 700° C. If such a lithium-nickel-containing composite oxide is used as the base material for a positive electrode active material, the crystal structure of the positive electrode active material may be destroyed due to phase transitions caused by charging and discharging, or the growth of primary particles may be insufficient.

[0103] In the present invention, the firing temperature is preferably set to 780°C or less. If the firing temperature exceeds 780°C, cation mixing is likely to occur, the layered structure in the crystal of the lithium nickel-containing composite oxide is broken, and the insertion and desorption of lithium ions may become difficult. In addition, as described below, it is preferable that the length of the lattice constant in the c-axis direction in the crystal of the lithium nickel-containing composite oxide obtained from the Rietveld analysis of X-ray diffraction is in the range of 14.183 Å to 14.205 Å, but if the firing temperature exceeds 780°C, the length of the lattice constant in the c-axis direction will not be 14.183 Å or more. Furthermore, the crystal of the lithium nickel-containing composite oxide may decompose, and nickel oxide or the like may be generated. In addition, the particles constituting the lithium nickel-containing composite oxide may sinter with each other to form coarse particles, and the average particle size of the lithium nickel-containing composite oxide may become too large.

[0104] From the above viewpoint, the firing temperature is preferably set in the range of 730°C to 760°C.

[0105] The retention time at such a firing temperature is preferably set in the range of 1 to 6 hours, and more preferably in the range of 2 to 4 hours. If the retention time is less than 1 hour, crystallization may be insufficient, and if it exceeds 6 hours, firing may proceed too far, causing cation mixing.

[0106] In order to remove water of crystallization and the like in the lithium compound and to uniformly react the lithium compound with the nickel compound in a temperature range in which crystal growth of the lithium-nickel-containing composite oxide proceeds, it is preferable to perform a two-stage firing process in which the passage and / or retention time in a temperature range of 400°C to 600°C is 1 to 5 hours, followed by retention time at a temperature of 700°C to 780°C for 3 hours or more.

[0107] In the present invention, in addition to these conditions, in the process of heating the lithium mixture from room temperature to a firing temperature of 700 ° C or more in an oxidizing atmosphere, the passing time and / or holding time in a temperature range where the material temperature of the lithium mixture is 600 ° C to 650 ° C are: More than 20 minutes 45 minutes or less, preferably 20 The range is from 1 to 40 minutes.

[0108] As described above, in the calcination process for obtaining a lithium nickel-containing composite oxide by calcining a lithium mixture, the calcination temperature of the lithium mixture, i.e., the maximum temperature at which the lithium mixture is held and the holding time thereof have been investigated. In addition, from the viewpoint of causing a uniform reaction between the lithium compound and the nickel compound, the passing time and / or holding time in the temperature range of 400°C to 600°C have also been investigated.

[0109] In response to this, the present inventors have focused on the reaction between Li of the lithium nickel-containing composite oxide and W of the tungsten compound when forming fine particles and / or a coating of a compound containing W and Li on the surface of the primary particles of the lithium nickel-containing composite oxide. From this viewpoint, the amount of excess Li in the lithium nickel-containing composite oxide as the base material and the firing conditions of this lithium nickel-containing composite oxide have been thoroughly studied. As a result, the present inventors have found that in the process of raising the temperature of the lithium mixture from room temperature to a firing temperature of 700°C or higher, in the temperature range of 600°C to 650°C where the generation of the lithium nickel-containing composite oxide progresses, there is a correlation between the passing time and / or holding time and the amount of excess Li present on the surface of the primary particles of the lithium nickel-containing composite oxide finally obtained, and that by appropriately controlling the amount of excess Li, it is possible to form fine particles and / or a coating of a compound containing W and Li without extracting Li present inside the primary particles of the lithium nickel-containing composite oxide in the reaction between Li of the lithium nickel-containing composite oxide and W of the tungsten compound.

[0110] In the past, in this temperature range, the heating rate was set to about 1° C. / min or less from the viewpoint of improving the crystallinity of the obtained lithium nickel-containing composite oxide, and the time for passing the lithium mixture in the temperature range of 600° C. to 650° C. was more than 45 minutes, for example, 50 minutes or more. However, if the time for passing in the temperature range of 600° C. to 650° C. exceeds 45 minutes, Li sufficiently enters the inside of the crystal of the primary particle in the process of generating the lithium nickel-containing composite oxide, and although the crystallinity is improved, the amount of excess Li present on the surface of the primary particle becomes insufficient. Therefore, when Li of the lithium nickel-containing composite oxide reacts with W of the tungsten compound, Li present inside the primary particle of the lithium nickel-containing composite oxide is extracted, and the amount of Li inside the primary particle of the obtained positive electrode active material becomes insufficient, which may deteriorate the battery characteristics.

[0111] The shorter the passage time of the lithium mixture in the temperature range of 600° C. to 650° C., the more the amount of excess Li in the lithium nickel-containing composite oxide that can react with W tends to increase. For this reason, the passage time in the temperature range of 600° C. to 650° C. is preferably 40 minutes or less, and more preferably 35 minutes or less. stomach. However, in view of the fact that the amount of surplus Li becomes excessive by shortening the time for passing the lithium compound in this temperature range, and the increase in the energy and equipment costs required for passing the lithium compound in a shorter time, the passing time in the temperature range of 600°C to 650°C is set to be shorter. 20 It is preferable that the time is 10 minutes or more.

[0112] In the present invention, the reason why the temperature range is not restricted by the temperature of the calcination furnace or the like but restricted by the material temperature is that the temperature is an important temperature range in which the production of the lithium nickel-containing composite oxide proceeds, and the range and transit time of the temperature range are short, so that it is preferable to restrict it by the temperature of the lithium mixture itself. Any device capable of measuring the temperature of the lithium mixture itself in the calcination furnace can be used to measure the material temperature, but a non-contact thermometer such as a thermocouple or a radiation thermometer can be used.

[0113] Moreover, since this temperature region is usually in the process of heating, the passage time in the temperature region of 600°C to 650°C can be set to 45 minutes or less by raising the temperature at a rate of 1.11°C / min or more. However, if the holding time in this temperature region is 45 minutes or less, the amount of excess Li present on the surface of the primary particles can be appropriately controlled. Therefore, it is within the scope of the present invention not only to pass through the temperature region at a constant heating rate, but also to raise the temperature stepwise or to hold at any temperature within the temperature region for a certain period of time.

[0114] 2. Manufacturing method of positive electrode active material for lithium-ion secondary batteries A second aspect of the present invention relates to a method for producing a positive electrode active material for a lithium ion secondary battery, i.e., a lithium-nickel-containing composite oxide coated with a compound containing W and Li, in which fine particles and / or a coating of a compound containing W and Li are present on the surfaces of primary particles.

[0115] The method for producing a positive electrode active material for a lithium ion secondary battery of the present invention comprises the steps of: Using the lithium nickel-containing composite oxide according to the first aspect of the present invention, a slurry is formed such that the amount of the lithium nickel-containing composite oxide is 700 g to 2000 g per 1 L of water, and the lithium nickel-containing composite oxide is washed with water; During or after the water washing treatment, a tungsten compound is added to the lithium nickel-containing composite oxide to disperse W on the surfaces of the primary particles of the lithium nickel-containing composite oxide; and The lithium nickel-containing composite oxide having W dispersed on the surfaces of the primary particles is heat-treated to form fine particles and / or a coating of a compound containing W and Li on the surfaces of the primary particles of the lithium nickel-containing composite oxide. It is characterized by:

[0116] [Washing process] The water-washing step is a step of washing the calcined powder of the lithium-nickel-containing composite oxide obtained in the calcination step with water. Specifically, a slurry is formed so that the calcined powder is 700 g to 2000 g per 1 L of water, and after washing with water, the slurry is filtered and dried to obtain the lithium-nickel-containing composite oxide powder (water-washed powder).

[0117] In the water washing step, the water washing temperature during the water washing treatment is adjusted to preferably be in the range of 10°C to 40°C, more preferably be in the range of 10°C to 30°C. This removes impurities present on the surface of the calcined powder of the lithium-nickel-containing composite oxide. The water washing treatment removes excess Li such as lithium carbonate and lithium hydroxide present on the surface together with the impurities. By performing the water washing under the above water washing conditions, even after water washing, the amount of excess Li is more than 0.10 mass%, preferably 0.15 mass% or more, more preferably 0.20 mass% or more, based on the entire lithium-nickel-containing composite oxide.

[0118] As a result, when forming fine particles and / or a coating of a compound containing W and Li on the surface of the primary particles of the lithium nickel-containing composite oxide, sufficient Li is present on the surface of the primary particles to react with W of the tungsten compound, and Li is not extracted from the inside by reaction with W. On the other hand, by appropriately regulating the amount of excess Li, no excess Li is present on the surface of the finally obtained positive electrode active material, so that when this positive electrode active material is used in the positive electrode of a lithium ion secondary battery, gas generation during high temperature retention can be suppressed, and high capacity, high output, and high safety can be achieved at the same time.

[0119] On the other hand, if the water washing temperature is less than 10°C, the washing is insufficient, and impurities adhering to the surface of the sintered powder may not be removed and remain. The presence of such remaining impurities increases the resistance of the surface of the positive electrode active material, which increases the resistance value of the positive electrode of the secondary battery. In addition, the specific surface area of ​​the positive electrode active material becomes too small, which reduces the reactivity with the electrolyte, making it difficult to achieve high capacity and high output of the secondary battery.

[0120] On the other hand, if the water washing temperature exceeds 40°C, the amount of Li eluted from the fired powder increases, and there is a risk that nickel oxide (NiO) from which Li has been removed or nickel oxyhydroxide (NiOOH) from which Li has been replaced with H will be produced in the surface layer of the lithium-nickel-containing composite oxide. Both nickel oxide and nickel oxyhydroxide have high electrical resistance, and they increase the resistance of the surface of the positive electrode active material, while also reducing Li in the positive electrode active material, reducing the capacity of the secondary battery.

[0121] The amount of the calcined powder per 1 L of water contained in the slurry is adjusted to 700 g to 2000 g, preferably 700 g to 1500 g.

[0122] That is, if the slurry concentration exceeds 2000 g / L, the viscosity of the slurry becomes high, making it difficult to stir. Furthermore, the alkali concentration of the liquid in the slurry becomes high, so that due to equilibrium, the dissolution rate of the deposits attached to the fired powder slows down, and even if the deposits peel off from the powder, they may reattach, making it difficult to remove impurities.

[0123] On the other hand, if the slurry concentration is less than 700g / L, it is too dilute, so a large amount of Li dissolves from the surface of each particle into the slurry. In particular, the higher the nickel ratio, the more Li dissolves and the less Li there is on the surface. This causes Li to be released from the crystal lattice of the lithium-nickel-containing composite oxide, making the crystals more likely to collapse. This reduces the capacity of the secondary battery.

[0124] The time for washing the sintered powder with water is not particularly limited, but is preferably about 5 to 60 minutes. If the washing time is too short, impurities on the powder surface may not be sufficiently removed and may remain. On the other hand, even if the washing time is extended, the washing effect is not improved and productivity decreases.

[0125] The water used to form the slurry is not particularly limited. However, in order to prevent a decrease in battery performance due to the adhesion of impurities to the positive electrode active material, water having an electrical conductivity of less than 10 μS / cm as measured is preferable, and water having an electrical conductivity of 1 μS / cm or less is more preferable.

[0126] [Drying process] The temperature and method for drying the lithium-nickel-containing composite oxide after washing are not particularly limited, but the drying temperature is preferably set in the range of 80° C. to 500° C., and more preferably in the range of 120° C. to 250° C. By setting the drying temperature at 80° C. or higher, the powder after washing can be dried in a short time, and the occurrence of a gradient in lithium concentration between the surface and the interior of the particles can be suppressed, thereby further improving the characteristics of the positive electrode active material.

[0127] On the other hand, near the surface of the sintered powder after washing with water, it is expected that the ratio is very close to the stoichiometric ratio, or that some Li has been removed to a state close to the charged state. Therefore, at temperatures exceeding 500°C, the crystal structure of the powder close to the charged state may collapse, leading to a deterioration in the electrical properties.

[0128] From these viewpoints, the drying temperature is preferably in the range of 80°C to 500°C, and more preferably in the range of 120°C to 250°C, taking into consideration the productivity and thermal energy costs.

[0129] As for the drying method, it is preferable to dry the filtered powder at a predetermined temperature using a dryer that can control the atmosphere to a gas atmosphere not containing compounds containing carbon and sulfur or a vacuum atmosphere.

[0130] [Tungsten addition process] The tungsten addition step is a step in which a tungsten compound is added to the powder during or after the water washing treatment, and W is dispersed on the surfaces of the primary particles.

[0131] That is, W can be added to the slurry during the water washing process, to the powder before drying after the water washing process, or to the powder dried after the water washing process. In any case, by controlling the moisture content of the powder after dehydration, it is possible to increase the uniformity of the dispersion of W and suppress the elution of Li, and form fine particles and / or a coating of a compound containing W and Li on the surface of the primary particles of the positive electrode active material.

[0132] The amount of W dispersed on the surfaces of the primary particles of the sintered powder is preferably in the range of 0.1 atomic % to 3.0 atomic %, and more preferably in the range of 0.1 atomic % to 1.0 atomic %, relative to the total number of atoms of Ni, Co, and M contained in the sintered powder. This allows fine particles and / or coatings of a compound containing W and Li to be more uniformly formed on the surfaces of the primary particles of the positive electrode active material, and when used in the positive electrode of a secondary battery, a conductive path for Li is formed at the interface with the electrolyte, reducing the reaction resistance of the positive electrode active material and further improving the output characteristics.

[0133] In addition, whether fine particles of a compound containing W and Li, a coating of a compound containing W and Li, or both are formed on the surface of the primary particles is determined by the moisture content of the powder after dehydration. When added to powder before drying after water washing treatment, the moisture content of the powder after dehydration is controlled to be in the range of 3.0 mass% to 11.5 mass%. When the moisture content of the powder is 3.0 mass% or more and less than 6.5 mass%, fine particles of a compound containing W and Li are formed on the surface of the primary particles. By making the moisture content of the powder 6.5 mass% or more, a coating of a compound containing W and Li tends to be formed on the surface of the primary particles, and the coating and the fine particles are mixed. By making the moisture content of the powder 9.0 mass% or more, only a coating of a compound containing W and Li can be formed on the surface of the primary particles. The moisture content after dehydration is calculated from the mass of the hydrous powder after dehydration and the mass of the powder after drying it at 180°C for 3 hours using the formula: "moisture content = (mass of hydrous powder before drying - mass of powder after drying) / (mass of hydrous powder before drying)".

[0134] W may be added to the slurry during the water-washing treatment, to the calcined powder after the water-washing treatment and before drying, or to the calcined powder after the water-washing treatment and drying.

[0135] W may be added either in the form of an alkaline solution in which a tungsten compound is dissolved (hereinafter referred to as "alkaline solution (W)"), or in the form of a tungsten compound.

[0136] When added as an alkaline solution (W), the tungsten compound may be any compound that is soluble in an alkaline solution, and it is preferable to use a tungsten compound that is easily soluble in an alkaline solution, such as tungsten oxide, lithium tungstate, or ammonium tungstate.

[0137] As the alkali used in the alkaline solution (W), in order to obtain a high charge / discharge capacity, a general alkaline solution that does not contain impurities harmful to the positive electrode active material, such as ammonia or lithium hydroxide, can be used. It is preferable to use lithium hydroxide in order to make it possible to supply a sufficient amount of Li to form a compound containing W and Li from the surplus Li and the alkaline solution (W) and from the viewpoint of not inhibiting the intercalation of Li.

[0138] On the other hand, when added in the form of a tungsten compound, it is preferable to use a tungsten compound that is soluble in alkali as the tungsten compound, it is more preferable to use a tungsten compound containing lithium, and it is even more preferable to use lithium tungstate. As the lithium tungstate, at least one selected from Li2WO4, Li4WO5, and Li6W2O9 can be used.

[0139] In either case, the addition of W requires that the treatment conditions and the means of addition are selected so that the amount of W in the fine particles and / or coating of the compound containing W and Li, such as lithium tungstate, formed on the surface of the particles constituting the lithium nickel-containing composite oxide by solid-liquid separation or crushing after heat treatment, falls within the range of the present invention. Note that these treatment conditions and means of addition are publicly known, and therefore a detailed description thereof will be omitted here.

[0140] [Heat treatment process] The heat treatment step is a step of forming fine particles and / or a coating of a compound containing W and Li on the surface of the primary particles of the lithium nickel-containing composite oxide by heat treating the lithium nickel-containing composite oxide having W dispersed on the surface of the primary particles. As a result, fine particles and / or a coating of a compound containing W and Li are formed from the W and Li supplied in the tungsten addition step, and a positive electrode active material for a lithium ion secondary battery is obtained, which is made of a lithium nickel-containing composite oxide coated with a compound containing W and Li, which has fine particles and / or a coating of a compound containing W and Li on the surface of the primary particles of the lithium nickel-containing composite oxide. Note that when W is added to the slurry during the water washing treatment or the calcined powder before drying after the water washing treatment, the drying step can be replaced by a heat treatment step.

[0141] The heat treatment method is not particularly limited, but in order to prevent deterioration of the electrical characteristics when used as a positive electrode active material for a lithium ion secondary battery, it is preferable to perform the heat treatment in an oxygen atmosphere or a vacuum atmosphere at a temperature in the range of 100°C to 600°C.

[0142] If the heat treatment temperature is less than 100°C, evaporation of water is insufficient, and fine particles and / or coating of the compound containing W and Li may not be formed sufficiently. On the other hand, if the heat treatment temperature exceeds 600°C, the primary particles of the lithium nickel-containing composite oxide may be sintered, and some W may be dissolved in the layered structure of the lithium nickel-containing composite oxide, resulting in a decrease in the charge / discharge capacity of the battery. From this viewpoint, the heat treatment temperature is more preferably 550°C or less, and even more preferably 500°C or less.

[0143] The atmosphere during the heat treatment is preferably an oxidizing atmosphere such as an oxygen atmosphere or a vacuum atmosphere in order to avoid reaction with moisture or carbon dioxide in the atmosphere.

[0144] The heat treatment time is not particularly limited, but is preferably within the range of 5 to 15 hours in order to sufficiently evaporate the moisture in the composite oxide particles and form a coating.

[0145] The moisture content of the composite oxide particles after drying is not particularly limited, but is preferably 0.2% by mass or less, and more preferably 0.1% by mass or less. If the moisture content of the powder exceeds 0.2% by mass, gas components containing carbon and sulfur in the air may be absorbed to produce lithium compounds on the surface.

[0146] When the particles aggregate after the heat treatment, they are crushed to a degree that does not destroy the secondary particle structure, to produce a positive electrode active material composed of particles having a volume-based average particle size MV in the range of 5 μm to 30 μm.

[0147] 3. Positive electrode active material for lithium-ion secondary batteries A third aspect of the present invention relates to a positive electrode active material for a lithium ion secondary battery, that is, a lithium-nickel-containing composite oxide coated with a compound containing W and Li, the compound having fine particles and / or a coating of a compound containing W and Li, such as lithium tungstate, present on its surface.

[0148] More specifically, the positive electrode active material for lithium ion secondary batteries of the present invention has fine particles of a compound containing W and Li or a coating of a compound containing W and Li formed on the surfaces of the primary particles constituting the lithium nickel-containing composite oxide as a base material and / or the surfaces of the primary particles constituting the secondary particles formed by agglomeration of the primary particles. In particular, the positive electrode active material for lithium ion secondary batteries of the present invention is characterized in that the lithium nickel-containing composite oxide is the lithium nickel-containing composite oxide of the first aspect of the present invention, that is, a lithium nickel-containing composite oxide obtained by adding 1.25 kg of the lithium nickel-containing composite oxide to 1 L of pure water, stirring, and filtering, and the electrical conductivity of the filtrate is in the range of 42.5 mS / cm to 62.5 mS / cm.

[0149] Regarding the characteristics of the base material, Already Therefore, a duplicated description will be omitted and the following will describe the fine particles and / or coating of a compound containing W and Li.

[0150] [Fine particles and / or coatings of compounds containing W and Li] Generally, when the surface of the positive electrode active material is completely covered with a different compound, the movement (intercalation) of lithium ions is greatly restricted, and as a result, the advantage of the lithium nickel-containing composite oxide, that is, high capacity, is eliminated.

[0151] In contrast, in the present invention, fine particles of a compound containing W and Li are formed on the surface of primary particles of a lithium-nickel-containing composite oxide, or a coating consisting of a compound containing W and Li and having a thickness in the range of 1 nm to 200 nm, preferably in the range of 1 nm to 150 nm, and more preferably in the range of 2 nm to 100 nm is formed on the surface of the primary particles.

[0152] The fine particles of the compound containing W and Li have high lithium ion conductivity and have the effect of promoting the movement of lithium ions. Therefore, by forming the fine particles of the compound containing W and Li on the surface of the primary particles, a conductive path of Li is formed at the interface with the electrolyte, so that it is possible to reduce the reaction resistance of the positive electrode active material (also called "positive electrode resistance") and improve the output characteristics. The coating of the compound containing W and Li also has the same effect as the fine particles of the compound containing W and Li by restricting its thickness to the range of 1 nm to 200 nm.

[0153] That is, by reducing the positive electrode resistance, the voltage loss in the secondary battery is reduced, and the voltage actually applied to the load side is relatively high, so that high output can be obtained. In addition, by increasing the voltage applied to the load side, lithium is sufficiently inserted and removed from the positive electrode, so that the battery capacity is improved. Furthermore, by reducing the positive electrode resistance, the load on the positive electrode active material during charging and discharging is also reduced, so that the cycle characteristics can be improved.

[0154] Here, if the surface of the primary particles constituting the positive electrode active material is excessively thickly coated with a compound containing W and Li, the specific surface area decreases, and even if the compound containing W and Li has high lithium ion conductivity, the contact area with the electrolyte becomes small, which tends to lead to a decrease in charge / discharge capacity and an increase in reaction resistance. In addition, although the presence of the compound containing W and Li reduces the reaction resistance, the compound containing W and Li itself has low electronic conductivity, so it reduces the electronic conductivity of the electrode, leading to a decrease in the output characteristics of the secondary battery.

[0155] In the present invention, by having fine particles made of a compound containing W and Li and having a predetermined particle size, or a coating made of a compound containing W and Li and having a film thickness in a predetermined range, present on the surface of primary particles, it is possible to effectively improve lithium ion conduction, suppress a decrease in charge / discharge capacity, and reduce reaction resistance without excessively reducing the electrode surface size or significantly increasing the bulk resistance of the electrode.

[0156] The particle diameter of the fine particles of the compound containing W and Li is preferably in the range of 1 nm to 100 nm. If the particle diameter is less than 1 nm, the fine particles may not have sufficient lithium ion conductivity. If the particle diameter exceeds 100 nm, the formation of the coating by the fine particles becomes non-uniform, and the effect of reducing the reaction resistance may not be sufficiently obtained. It is not necessary that all the fine particles have a particle diameter in the range of 1 nm to 100 nm, and preferably, if 50% or more of the total number of the fine particles formed on the surface of the primary particle have a particle diameter in the range of 1 nm to 100 nm, a higher effect of improving the battery characteristics can be obtained. In this case, the maximum particle diameter of the fine particles is about 200 nm.

[0157] The coating of the compound containing W and Li preferably has a thickness in the range of 1 nm to 200 nm. If the thickness is less than 1 nm, the coating may not have sufficient lithium ion conductivity. If the thickness exceeds 200 nm, the reaction area may decrease and the bulk resistance of the electrode may increase, and the effect of reducing the reaction resistance may not be sufficiently obtained.

[0158] Since contact with the electrolyte occurs on the surface of the primary particles, it is important that fine particles and / or a coating of a compound containing W and Li are formed on the surface of the primary particles. Here, the surface of the primary particles in the present invention refers to the surface of the primary particles when the lithium nickel-containing composite oxide is composed of primary particles. When the lithium nickel-containing composite oxide is composed of secondary particles, the surface of the primary particles includes both the surface of the primary particles exposed on the outer surface of the secondary particles and the surface vicinity and internal voids of the secondary particles through which the electrolyte can penetrate through the secondary particles. Furthermore, even if the grain boundary between the primary particles is incompletely bonded and the electrolyte can penetrate, such a portion is also included in the surface of the primary particles.

[0159] Therefore, by forming fine particles and / or a coating of a compound containing W and Li over the entire surface of the primary particles, it is possible to further promote the movement of lithium ions and further reduce the reaction resistance of the particles that make up the positive electrode active material.

[0160] It is not necessary that the fine particles and / or coating of the compound containing W and Li are formed on the entire surface of the primary particles that can contact the electrolyte. The fine particles and / or coating of the compound containing W and Li may be in a scattered state, and even in a scattered state, as long as the fine particles and / or coating of the compound containing W and Li are formed on the surface of the primary particles constituting the positive electrode active material, or the surface of the primary particles exposed to the outer surface and internal voids of the secondary particles constituting the positive electrode active material, the effect of reducing reaction resistance can be obtained. However, the higher the proportion of these on the surface of the primary particles, the easier it is to obtain the effect of reducing reaction resistance.

[0161] On the other hand, if the fine particles are formed non-uniformly between the particles constituting the lithium nickel-containing composite oxide, the movement of lithium ions between the particles becomes non-uniform, so that a load is applied to certain particles, which is likely to cause deterioration of cycle characteristics and an increase in reaction resistance. Therefore, it is preferable that the fine particles are formed uniformly between the particles constituting the lithium nickel-containing composite oxide.

[0162] Also, when the fine particles of the compound containing W and Li are mixed with the coating and formed on the surface of the primary particle, a high effect on the battery characteristics can be obtained. In this case, in order to obtain a higher effect of improving the battery characteristics, it is preferable that the fine particles of the compound containing W and Li have a particle diameter in the range of 1 nm to 200 nm. It is not necessary that all the fine particles have a particle diameter in the range of 1 nm to 200 nm, and preferably, if 50% or more of the total number of the fine particles formed on the surface of the primary particle have a particle diameter in the range of 1 nm to 200 nm, a higher effect of improving the battery characteristics can be obtained by interaction with the coating.

[0163] By adopting such a configuration, the contact area with the electrolyte can be made sufficient, and lithium ion conduction can be effectively improved, thereby improving the charge / discharge capacity and more effectively reducing the reaction resistance.

[0164] The surface properties of such primary particles can be determined, for example, by cross-sectional observation with a field emission scanning electron microscope, cross-sectional element mapping by EDX analysis with a scanning transmission electron microscope (STEM), cross-sectional observation with a transmission ionization microscope, etc. By these means, it is possible to confirm that, for the positive electrode active material for lithium ion secondary batteries of the present invention, fine particles and / or a coating of a compound containing W and Li are formed on the surfaces of the primary particles constituting the lithium nickel-containing composite oxide.

[0165] In the present invention, the compound containing W and Li constituting the fine particles and / or coating of the compound containing W and Li is preferably lithium tungstate. Lithium tungstate is Li2WO4, Li4WO5, Li6WO6, Li2W4O 13 , Li2W2O7, Li6W2O9, Li2W2O7, Li2W5O 16 , Li9W 19 O 55 , Li3W 10 O 30 , Li 18 W5O 15 and hydrates thereof. By forming such lithium tungstate, the lithium ion conductivity is further increased, and the effect of reducing the reaction resistance is further increased.

[0166] The number of W atoms contained in the compound containing W and Li is preferably in the range of 0.1 atomic % to 3.0 atomic %, more preferably in the range of 0.1 atomic % to 1.0 atomic %, and even more preferably in the range of 0.1 atomic % to 0.6 atomic %, relative to the total number of Ni, Co, and M atoms contained in the particles constituting the positive electrode active material. This makes it possible to achieve both high charge / discharge capacity and output characteristics.

[0167] If the W content is less than 0.1 atomic %, the effect of improving the output characteristics may not be sufficient.If the W content exceeds 3.0 atomic %, the surface of the primary particles is covered too thickly with fine particles and / or films of compounds containing W and Li, the specific surface area decreases, and the bulk resistance of the electrode increases, so that the effect of reducing the reaction resistance may not be sufficient.

[0168] The amount of Li contained in the fine particles and / or coating of the compound containing W and Li is not particularly limited, and the effect of improving lithium ion conductivity can be obtained as long as Li is contained. However, it is preferable that the amount of Li is sufficient to form lithium tungstate.

[0169] When the amount of W is in the range of 0.1 atomic % to 3.0 atomic %, the positive electrode active material is General formula: Li a Ni 1―x―y Co x M y W z O 2+α (2) (In the formula, M is at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo, and W. 0.95≦a≦1.10, 0 <x≦0.15、0<y≦0.07、x+y≦0.16、0.001≦z≦0.03、0≦α≦0.2である。) It is preferable that the lithium nickel-containing composite oxide has a composition consisting of the following: Note that W can be contained inside the lithium nickel-containing composite oxide as an additive element M, but in this case, the amount of W (z in the composition formula) does not include the amount of W contained as the additive element M.

[0170] a representing the Li content satisfies 0.95 ≦ a ≦ 1.10. When a exceeds 1.10, the Li content in the lithium nickel-containing composite oxide becomes too high, and Li may be mixed into the metal layer in the layered compound. On the other hand, when a is 0.95 or less, metal elements such as Ni may be mixed into the lithium layer. Therefore, in order to improve the battery capacity and output characteristics, it is more preferable that 0.95 < a ≦ 1.08. z representing the content of W is preferably 0.001 ≦ z ≦ 0.01.

[0171] 4. Lithium Ion Secondary Battery The lithium ion secondary battery obtained by using the positive electrode active material for the lithium ion secondary battery of the present invention is composed of a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte, etc., in the same manner as a general lithium ion battery. For example, the 2032 type coin battery 1 shown in FIG. 1 (hereinafter referred to as "coin type battery") is composed of a case 2 and an electrode 3 housed in this case 2.

[0172] The case 2 has a hollow positive electrode can 2a with one end opened and a negative electrode can 2b disposed at the opening of the positive electrode can 2a. When the negative electrode can 2b is disposed at the opening of the positive electrode can 2a, a space for housing the electrode 3 is formed between the negative electrode can 2b and the positive electrode can 2a.

[0173] The electrode 3 is composed of a positive electrode 3a, a separator 3c, and a negative electrode 3b, and is laminated in this order so as to be arranged in a row. The positive electrode 3a is in contact with the inner surface of the positive electrode can 2a, and the negative electrode 3b is in contact with the inner surface of the negative electrode can 2b, and are respectively housed in the case 2.

[0174] Note that the case 2 is provided with a gasket 2c, and the relative movement between the positive electrode can 2a and the negative electrode can 2b is blocked by this gasket 2c so as to maintain a non-contact state therebetween. Further, the gasket 2c also has a function of sealing the gap between the positive electrode can 2a and the negative electrode can 2b to hermetically block the inside of the case 2 from the outside in terms of airtightness and liquid tightness.

[0175] The embodiments described below are merely examples, and the lithium ion secondary battery of the present invention can be embodied in various forms that are modified and improved based on the embodiments described in this specification and the knowledge of those skilled in the art. Furthermore, the lithium ion secondary battery of the present invention is not particularly limited in its use.

[0176] [Positive electrode] The lithium nickel-containing composite oxide of the present invention can be used as a positive electrode active material constituting a positive electrode, and a positive electrode of a lithium ion secondary battery can be produced, for example, as follows.

[0177] First, a powdered positive electrode active material, a conductive agent, and a binder are mixed, and a slurry solvent and, if necessary, activated carbon and a viscosity adjusting additive are added, and the mixture is kneaded to prepare a positive electrode mixture paste.

[0178] The mixing ratio of each component in the positive electrode mixture paste is also an important factor that determines the performance of the lithium ion secondary battery. When the total mass of the solid content of the positive electrode mixture excluding the solvent is 100 parts by mass, it is preferable that the content of the positive electrode active material is 60 parts by mass to 95 parts by mass, the content of the conductive agent is 1 part by mass to 20 parts by mass, and the content of the binder is 1 part by mass to 20 parts by mass, similar to the positive electrode of a general lithium ion secondary battery.

[0179] The obtained positive electrode mixture paste is applied, for example, to the surface of a current collector and dried to evaporate the slurry solvent. If necessary, pressure can be applied by a roll press or the like to increase the electrode density. In this way, a sheet-shaped positive electrode is produced.

[0180] The sheet-like positive electrode is cut to an appropriate size depending on the intended battery, and used to fabricate the battery. However, the method for fabricating the positive electrode is not limited to the exemplified method, and other methods may be used.

[0181] The conductive agent is not particularly limited as long as it is an electronically conductive material that is chemically stable in the battery. For example, graphites such as natural graphite (e.g., flake graphite) and artificial graphite, carbon blacks such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, conductive fibers such as carbon fiber and metal fiber, metal powders such as aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, organic conductive materials such as polyphenylene derivatives, and carbon fluoride can be used. These may be used alone or in combination of two or more.

[0182] The amount of the conductive agent added to the positive electrode mixture is not particularly limited, but is preferably in the range of 0.5 mass % to 50 mass %, more preferably in the range of 0.5 mass % to 30 mass %, and even more preferably in the range of 0.5 mass % to 15 mass %, relative to the positive electrode active material contained in the positive electrode mixture.

[0183] The binder serves to bind the active material particles together. Examples of the binder include polyethylene, polypropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene butadiene rubber, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, ethylene-tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), vinylidene fluoride-pentafluoropropylene copolymer, propylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer (ECTFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, vinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl acrylate copolymer, and ethylene-methyl methacrylate copolymer.

[0184] The above resins may be used alone or in combination of two or more. + It may be a crosslinked body using ions or the like.

[0185] Specifically, an organic solvent such as N-methyl-2-pyrrolidone can be used as the paste solvent. Activated carbon can also be added to the positive electrode mixture to increase the electric double layer capacity.

[0186] The current collector is not particularly limited as long as it is an electronic conductor that is chemically stable in the battery. For example, a foil or sheet made of aluminum, stainless steel, nickel, titanium, carbon, conductive resin, etc. can be used, and among these, aluminum foil, aluminum alloy foil, etc. are more preferable. A carbon or titanium layer can be applied to the surface of the foil or sheet, or an oxide layer can be formed. In addition, the surface of the foil or sheet can be unevenly provided, and a net, a punched sheet, a lath body, a porous body, a foam body, a fiber group molded body, etc. can be used. The thickness of the current collector is not particularly limited, but is preferably in the range of 1 μm to 500 μm.

[0187] (2) Negative electrode The negative electrode can be made of metallic lithium, a lithium alloy, etc. For example, the negative electrode can be made by mixing a binder with a negative electrode active material capable of absorbing and desorbing lithium ions, adding an appropriate solvent to make a paste-like negative electrode mixture, applying the mixture to the surface of a metal foil collector such as copper, drying it, and compressing it to increase the electrode density as necessary.

[0188] As the negative electrode active material, for example, natural graphite, artificial graphite, a calcined organic compound such as phenolic resin, or a powder of a carbon material such as coke can be used. In this case, as with the positive electrode, as the negative electrode binder, a fluorine-containing resin such as PVDF can be used, and as the solvent for dispersing these active materials and binders, an organic solvent such as N-methyl-2-pyrrolidone can be used.

[0189] (3) Separator A separator is sandwiched between the positive and negative electrodes. The separator electrically separates the positive and negative electrodes, holds the electrolyte, and acts as a path for lithium ions to move between the positive and negative electrodes. A typical separator is a thin membrane made of polyethylene, polypropylene, or the like, that has many tiny pores. A solid electrolyte can also be used.

[0190] The separator may be made of a microporous thin film. In this case, the pore size of the pores formed in the separator is not particularly limited, but is preferably in the range of 0.01 μm to 1 μm, for example. The porosity of the separator is not particularly limited, but is generally about 30% to 80%. The thickness of the separator is not particularly limited, but is generally about 10 μm to 300 μm.

[0191] Furthermore, the separator may be separate from the positive and negative electrodes, but a polymer electrolyte made of a non-aqueous electrolyte and a polymer material that holds the non-aqueous electrolyte may be integrated with the positive or negative electrode to be used as the separator. The polymer material may be any material capable of holding the non-aqueous electrolyte, and is not particularly limited, but is preferably a copolymer of vinylidene fluoride and hexafluoropropylene.

[0192] (4) Nonaqueous electrolyte As the non-aqueous electrolyte, in addition to a non-aqueous electrolytic solution obtained by dissolving a lithium salt, which is a supporting salt, in an organic solvent, a non-flammable solid electrolyte having ion conductivity, or the like, can be used. A non-aqueous electrolyte solution that is widely used as a non-aqueous electrolyte for lithium ion secondary batteries is prepared by dissolving a lithium salt as a supporting salt in an organic solvent. The organic solvent used is, for example, Cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, trifluoropropylene carbonate; Chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; Aliphatic carboxylates such as methyl formate, methyl acetate, methyl propionate, and ethyl propionate; Lactones such as gamma-butyrolactone and gamma-valerolactone; Chain ethers such as 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), and ethoxymethoxyethane (EME); Ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; Sulfur compounds such as ethyl methyl sulfone and butane sultone; Phosphorus compounds such as triethyl phosphate and trioctyl phosphate; Dimethyl sulfoxide, 1,3-dioxolane, formamide, acetamide, dimethylformamide, dioxolane, acetonitrile, propylnitrile, nitromethane, ethyl monoglyme, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, 3-methyl-2-oxazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethyl ether, 1,3-propane sultone, anisole, dimethyl sulfoxide, N-methyl-2-pyrrolidone, etc.; These may be used alone or in combination of two or more.

[0193] The supporting salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, LiAlCl4, LiSbF6, LiSCN, LiCl, LiCF3SO3, LiCF3CO2, Li(CF3SO2)2, LiB 10 Cl 10 , lower aliphatic carboxylate lithium, LiCl, LiBr, LiI, chloroborane lithium, tetraphenylborate lithium, lithium imide salts, etc. These may be used alone or in combination of two or more. It is preferable to use at least LiPF6.

[0194] The lithium salt concentration in the non-aqueous solvent is not particularly limited, but is preferably in the range of 0.2 mol / L to 2 mol / L, and more preferably in the range of 0.5 mol / L to 1.5 mol / L.

[0195] Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like.

[0196] On the other hand, as a solid electrolyte, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li2S-SiS2 can be used.

[0197] [Shape and composition of lithium-ion secondary batteries] The lithium ion secondary battery of the present invention, which is composed of the positive electrode, negative electrode, separator, and non-aqueous electrolyte described above, can have various shapes such as a cylindrical type or a laminated type.

[0198] Regardless of the shape adopted, for example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the positive electrode and the negative electrode are laminated with a separator interposed therebetween to form an electrode body, the obtained electrode body is impregnated with the non-aqueous electrolyte solution, the positive electrode current collector and the positive electrode terminal connected to the outside, and the negative electrode current collector and the negative electrode terminal connected to the outside are connected using a current collecting lead or the like, and the battery is sealed in a battery case to complete the lithium ion secondary battery.

[0199] [Characteristics of lithium-ion secondary batteries] A lithium ion secondary battery using the W- and Li-containing compound-coated lithium nickel-containing composite oxide of the present invention, in which fine particles and / or a coating of a compound containing W and Li are present on the surfaces of the primary particles, as a positive electrode active material has high capacity and high output.

[0200] In particular, a lithium ion secondary battery using the positive electrode active material for lithium ion secondary batteries of the present invention obtained in a more preferred form, when used in the positive electrode of a coin-type battery as shown in FIG. 1, has a high initial discharge capacity of 200 mAh / g or more, preferably 205 mAh / g or more, and a high initial charge / discharge efficiency of 88% or more, resulting in high capacity and high output. EXAMPLES

[0201] The present invention will be specifically described below using examples, but the present invention is not limited by these examples. In the present examples, the nickel compound, cobalt compound, compound of additive element M, and lithium compound, which are precursors, and the materials used in the manufacture of the lithium nickel-containing composite oxide and lithium ion secondary battery are all reagent grade samples manufactured by Wako Pure Chemical Industries, Ltd.

[0202] Example 1 [Production and evaluation of lithium nickel-containing composite oxides] The temperature in the reaction tank was set to 49.5°C, and while the reaction solution in the reaction tank was maintained at pH 13.0 at a liquid temperature of 25°C using a 20% by mass sodium hydroxide solution, a mixed aqueous solution of nickel sulfate and cobalt sulfate, an aqueous sodium aluminate solution, and 25% by mass aqueous ammonia were added to the reaction solution and collected by overflow. The solution was further washed with a 45 g / L aqueous sodium hydroxide solution with a pH of 12.5 at a liquid temperature of 25°C, then washed with water and dried to obtain a nickel composite hydroxide (neutralization crystallization method).

[0203] This nickel composite hydroxide is composed of secondary particles formed by the aggregation of multiple primary particles smaller than 1 μm into a spherical shape, and analysis by ICP optical emission spectrometry using an ICP optical emission spectrometer (Shimadzu Corporation, ICPE-9000) confirmed that it was a nickel composite hydroxide with a molar ratio of Ni:Co:Al of 90.5:4.8:4.7.

[0204] The volume-based average particle size MV of this nickel composite hydroxide was measured using a laser light diffraction scattering type particle size analyzer (Microtrack HRA, manufactured by Nikkiso Co., Ltd.), and was found to be 12 μm.

[0205] In addition, sulfur was quantitatively analyzed by ICP atomic emission spectrometry, and the sulfate ion content was calculated by multiplying a coefficient assuming that all sulfur is oxidized to sulfate ion (SO4), and was found to be 0.28 mass%.

[0206] Next, this nickel composite hydroxide was oxidized and roasted at a temperature of 600°C in an air atmosphere to obtain a nickel composite oxide, and then the nickel composite oxide and lithium hydroxide monohydrate were weighed out so that the molar ratio was Ni:Co:Al:Li = 90.5:4.8:4.7:1.02, and mixed using a shaker mixer (TURBULA Type T2C manufactured by Willy & Bachofen (WAB)) to obtain a lithium mixture.

[0207] The obtained lithium mixture was calcined at 500°C for 3 hours in an oxygen atmosphere using an electric furnace, then heated from 500°C to 745°C at a heating rate of 2.5°C / min so that the time to pass through the temperature range of 600°C to 650°C was 20 minutes, and then held at 745°C for 3 hours, and sintered for 20 hours from the start of heating to the end of holding. After that, it was cooled to room temperature in the furnace and crushed to obtain a sintered powder (hereinafter referred to as "base material"). In the sintering process, a thermocouple was inserted into the lithium mixture to measure the temperature of the mixture itself.

[0208] The obtained base material was analyzed by ICP method, and it was confirmed that the molar ratio of Ni:Co:Al:Li was 90.5:4.8:4.7:1.02. In addition, 1.25 g of the base material was taken out and put into 1 L of pure water kept at 25 ° C., stirred with a magnetic stirrer and a stirrer, stirred for 3 minutes, and then vacuum filtered. The conductivity of the obtained filtrate was measured using a conductivity meter (ES-71, manufactured by Horiba, Ltd.). As a result, the conductivity of the filtrate of this base material was 45 mS / cm.

[0209] Next, 20°C pure water was added to the obtained base material to prepare a slurry containing 750 g of base material per 1 L of water. After stirring this slurry for 20 minutes, it was passed through a filter press and dehydrated to produce a base material cake.

[0210] W was added to this base material by passing an alkaline solution (W) containing a tungsten compound through the base material cake after dehydration in a filter press, dehydrating it again, and dispersing W on the surface of the primary particles of the base material.

[0211] The amount of tungsten compound to be added is determined by the tungsten concentration in the alkaline solution (W) and the moisture content of the base cake after dehydration. In other words, the amount of tungsten contained in the moisture after dehydration is the amount to be added.

[0212] In this example, an alkaline solution (W) with a tungsten concentration of 0.58 mol / L was used, which was made by adding 131.8 g of tungsten oxide (WO3) to an aqueous solution of 50.6 g of lithium hydroxide (LiOH·H2O) dissolved in 1 L of pure water. The moisture content of the base cake after dehydration was 6.1%.

[0213] The obtained lithium nickel-containing composite oxide infiltrated with the alkaline solution (W) was subjected to a process of standing and drying for 10 hours using a vacuum dryer heated to 190°C.

[0214] Finally, the mixture was sieved through a sieve with 38 μm openings and crushed to obtain a positive electrode active material having fine particles and a coating of a compound containing W and Li on the surfaces of the primary particles.

[0215] The composition of the obtained positive electrode active material was analyzed by ICP emission spectrometry, and it was confirmed that the molar ratio of Ni:Co:Al:Li was 90.5:4.8:4.7:0.98, and the W content was 0.35 atomic % relative to the total number of Ni, Co, and Al atoms. It was also confirmed that the fine particles and coating of a compound containing W and Li on the surface of the primary particles consisted of lithium tungstate (Li2WO4).

[0216] The specific surface area of ​​the obtained positive electrode active material by the BET method was 0.93 m 2 / g.

[0217] This positive electrode active material was embedded in a resin and processed with a cross-section polisher, and cross-sectional observation was performed with a SEM at a magnification of 5000 times, confirming that it was made up of primary particles and secondary particles formed by aggregation of the primary particles. The porosity of the secondary particles obtained from this observation was 2.1%. In addition, after making this positive electrode active material in a state where cross-sectional observation was possible with a scanning transmission electron microscope (STEM: S-4700, manufactured by Hitachi High-Technologies Corporation), the surface vicinity of the primary particles was observed with the STEM, and it was confirmed that fine particles with a particle diameter in the range of 10 nm to 200 nm and a coating with a thickness in the range of 2 nm to 115 nm were formed on the surface of the primary particles. Furthermore, the results of powder XRD analysis using an X-ray diffraction (XRD) device (X'Pert PRO, manufactured by PANalytical Co., Ltd.) confirmed that these fine particles and coating were made of lithium tungstate.

[0218] [Production and evaluation of lithium-ion batteries] The coin-type battery 1 shown in FIG. 1 was fabricated as follows. First, 90 parts by mass of a positive electrode active material for lithium-ion secondary batteries, 5 parts by mass of acetylene black, and 5 parts by mass of polyvinylidene fluoride were mixed, and n-methylpyrrolidone was added to form a paste. This paste was applied to an aluminum foil having a thickness of 20 μm. The paste had a mass of the positive electrode active material of 0.05 g / cm after drying. 2 Thereafter, the aluminum foil on which the paste was applied was vacuum dried at 120° C. for 12 hours, and then punched out into a disk shape having a diameter of 1 cm to form a positive electrode 3a.

[0219] Using this positive electrode 3a, a negative electrode 3b, a separator 3c and a non-aqueous electrolyte, the coin-type battery 1 shown in FIG. 1 was fabricated in a glove box in an Ar atmosphere with a dew point controlled at -80°C.

[0220] For the negative electrode 3b, lithium metal punched into a disk shape having a diameter of 15 mm was used.

[0221] For the separator 3c, a polyethylene porous film having a thickness of 20 μm was used.

[0222] The electrolyte used was an equal mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (manufactured by Ube Industries, Ltd.) with 1M LiClO4 as the supporting electrolyte.

[0223] The initial discharge capacity, initial charge / discharge efficiency, and positive electrode resistance, which indicate the performance of the manufactured coin battery 1, were evaluated as follows.

[0224] The initial charge capacity and initial discharge capacity were measured by leaving the coin cell 1 for about 24 hours after production, and after the open circuit voltage (OCV) had stabilized, applying a current density of 0.1 mA / cm 2 The capacity when the battery was charged to a cutoff voltage of 4.3 V was defined as the initial charge capacity, and the capacity when the battery was discharged to a cutoff voltage of 3.0 V after a 1-hour rest was defined as the initial discharge capacity. [(initial discharge capacity) / (initial charge capacity)]×100 was calculated as the initial charge / discharge efficiency.

[0225] When the positive electrode resistance is measured by an AC impedance method using a frequency response analyzer and a potentiogalvanostat (Solartron, 1255B) while charging the coin battery 1 at a charging potential of 4.1 V, a Nyquist plot as shown in FIG. 2 is obtained.

[0226] Since this Nyquist plot is expressed as the sum of characteristic curves showing the solution resistance, the negative electrode resistance and its capacity, and the positive electrode resistance and its capacity, a fitting calculation was performed using an equivalent circuit based on this Nyquist plot to calculate the value of the positive electrode resistance.

[0227] The coin-type battery 1 using a positive electrode produced using the obtained positive electrode active material for lithium-ion secondary batteries had an initial discharge capacity of 205 mAh / g, an initial charge / discharge efficiency of 89.0%, and a positive electrode resistance of 4.8 Ω.

[0228] The firing conditions for the lithium nickel-containing composite oxide, the characteristics of the obtained lithium nickel-containing composite oxide, and the battery characteristics of the lithium ion secondary battery are shown in Table 1. The results of Example 2 and Comparative Examples 1 and 2 below are also shown in Table 1.

[0229] Example 2 A lithium nickel-containing composite oxide, a positive electrode active material for a lithium ion secondary battery, and a lithium ion secondary battery were produced and evaluated in the same manner as in Example 1, except that the temperature was raised from 500°C to 745°C at a heating rate of 1.43°C / min so that the transit time in the temperature range of 600°C to 650°C was 35 minutes. The composition of the obtained lithium nickel-containing composite oxide was represented by the general formula: Li 1.02 Ni 0.905 Co 0.048 Al 0.047 The conductivity of the filtrate of the base material was 60 mS / cm. The composition of the obtained positive electrode active material for lithium ion secondary batteries was represented by the general formula: Li 0.99 Ni 0.905 Co 0.048 Al 0.047 W 0.0035 The initial discharge capacity of the coin-type battery 1 using the positive electrode produced using the obtained positive electrode active material for lithium-ion secondary batteries was 208 mAh / g, the initial charge / discharge efficiency was 90.0%, and the positive electrode resistance was 4.6 Ω.

[0230] Comparative Example 1 A lithium nickel-containing composite oxide, a positive electrode active material for a lithium ion secondary battery, and a lithium ion secondary battery were produced and evaluated in the same manner as in Example 1, except that the temperature was raised from 500°C to 745°C at a heating rate of 0.91°C / min so that the transit time in the temperature range of 600°C to 650°C was 55 minutes. The composition of the obtained lithium nickel-containing composite oxide was represented by the general formula: Li 1.02 Ni 0.905 Co 0.048 Al 0.047 The conductivity of the filtrate of the base material was 40 mS / cm. The composition of the positive electrode active material for lithium ion secondary batteries obtained was represented by the general formula: Li0.99 Ni 0.905 Co 0.048 Al 0.047 W 0.0035 The initial discharge capacity of the coin-type battery 1 using the positive electrode produced using the obtained positive electrode active material for lithium-ion secondary batteries was 198 mAh / g, the initial charge / discharge efficiency was 85.0%, and the positive electrode resistance was 5.7 Ω.

[0231] Comparative Example 2 A lithium nickel-containing composite oxide, a positive electrode active material for a lithium ion secondary battery, and a lithium ion secondary battery were produced and evaluated in the same manner as in Example 1, except that the temperature was raised from 500°C to 745°C at a heating rate of 5.0°C / min so that the transit time in the temperature range of 600°C to 650°C was 10 minutes. The composition of the obtained lithium nickel-containing composite oxide was represented by the general formula: Li 1.02 Ni 0.905 Co 0.048 Al 0.047 The conductivity of the filtrate from the base material was 65 mS / cm. The composition of the positive electrode active material for lithium ion secondary batteries obtained was represented by the general formula: Li 0.99 Ni 0.905 Co 0.048 Al 0.047 W 0.0035 The initial discharge capacity of the coin-type battery 1 using the positive electrode produced using the obtained positive electrode active material for lithium-ion secondary batteries was 197 mAh / g, the initial charge / discharge efficiency was 84.0%, and the positive electrode resistance was 6.0 Ω.

[0232] [Table 1] [Industrial Applicability]

[0233] By obtaining a positive electrode active material for a lithium ion secondary battery using the lithium nickel-containing composite oxide of the present invention as a base material, in which fine particles and / or a coating of a compound containing W and Li are present on the surfaces of the primary particles, a positive electrode active material with high capacity and high output can be provided without impairing crystallinity. Such a high-quality positive electrode active material with excellent electrical properties is suitable as a positive electrode material for lithium ion secondary batteries used as power sources for electric vehicles, hybrid vehicles, etc. [Explanation of symbols]

[0234] 1 coin cell battery 2 Cases 2a Positive electrode can 2b Negative electrode can 2c Gasket 3 electrodes 3a positive electrode 3b negative electrode 3c Separator

Claims

1. A lithium-nickel-containing composite oxide which is a base material for a positive electrode active material for a lithium ion secondary battery and which is made of a lithium-nickel-containing composite oxide coated with a compound containing W and Li, the lithium-nickel-containing composite oxide being composed of primary particles and / or secondary particles formed by agglomeration of the primary particles, and in which fine particles and / or coatings of a compound containing W and Li are present on the surfaces of the primary particles, 1.25 kg of the lithium nickel-containing composite oxide is added to 1 L of pure water, stirred, and filtered to obtain a filtrate having an electrical conductivity in the range of 42.5 mS / cm to 62.5 mS / cm. Lithium nickel-containing composite oxide.

2. The lithium nickel-containing composite oxide described in claim 1, wherein the conductivity of the filtrate is in the range of 45 mS / cm to 60 mS / cm.

3. The length of the lattice constant in the c-axis direction in the crystal of the lithium nickel-containing composite oxide obtained by Rietveld analysis of X-ray diffraction is in the range of 14.183 Å to 14.205 Å. The lithium nickel-containing composite oxide according to claim 1 or 2.

4. The lithium nickel-containing composite oxide according to claim 1, having a volume-based average particle size MV in the range of 5 μm to 30 μm.

5. A method for producing a positive electrode active material for a lithium ion secondary battery comprising a lithium nickel-containing composite oxide coated with a compound containing W and Li, the lithium nickel-containing composite oxide comprising primary particles and / or secondary particles formed by agglomeration of the primary particles, and fine particles and / or a coating of a compound containing W and Li present on the surfaces of the primary particles, comprising: The lithium nickel-containing composite oxide according to any one of claims 1 to 4 is prepared by mixing a nickel compound and a lithium compound to obtain a lithium mixture, and then heating the lithium mixture in an oxidizing atmosphere from room temperature to a firing temperature of 700°C or higher, wherein the lithium mixture is passed through and / or held in a temperature range of 600°C to 650°C for 20 minutes or more and 45 minutes or less; Using the lithium nickel-containing composite oxide as a base material, a slurry is formed such that the amount of the lithium nickel-containing composite oxide is 700 g to 2000 g per 1 L of water, and the lithium nickel-containing composite oxide is washed with water; During or after the water washing treatment, a tungsten compound is added to the lithium nickel-containing composite oxide to disperse W on the surfaces of the primary particles of the lithium nickel-containing composite oxide; and The lithium nickel-containing composite oxide having W dispersed on the surfaces of the primary particles is heat-treated to form fine particles of a compound containing W and Li, or a coating of a compound containing W and Li, on the surfaces of the primary particles of the lithium nickel-containing composite oxide. Characterized in that A method for producing a positive electrode active material for a lithium ion secondary battery.

6. The positive electrode active material for a lithium ion secondary battery, General formula: Li a Ni 1-x-y Co x M y W z O 2+α ...(2) (In the formula, M is at least one element selected from Mg, Al, Ca, Ti, V, Cr, Mn, Nb, Zr, Mo, and W; 0.95≦a≦1.10, 0<x≦0.15, 0<y≦0.07, x+y≦0.16, 0.001≦z≦0.03, and 0≦α≦0.2.) The composition is a lithium nickel-containing composite oxide coated with a compound containing W and Li, The method for producing the positive electrode active material for a lithium ion secondary battery according to claim 5 .

7. A method for producing a positive electrode active material for a lithium ion secondary battery as described in claim 6, wherein the amount of W dispersed on the surface of a primary particle of the lithium nickel-containing composite oxide is in the range of 0.1 atomic % to 3.0 atomic % relative to the total number of Ni, Co and M atoms contained in the lithium nickel-containing composite oxide.

8. A method for producing a positive electrode active material for a lithium ion secondary battery described in any one of claims 5 to 7, wherein the heat treatment is carried out in an oxygen atmosphere or a vacuum atmosphere at a temperature in the range of 100°C to 600°C.

9. A positive electrode active material for a lithium ion secondary battery, comprising a lithium nickel-containing composite oxide coated with a compound containing W and Li, the lithium nickel-containing composite oxide comprising primary particles and / or secondary particles formed by agglomeration of the primary particles, the primary particles having fine particles and / or a coating of a compound containing W and Li on the surfaces thereof, The lithium nickel-containing composite oxide coated with a compound containing W and Li is characterized in that fine particles and / or a coating of a compound containing W and Li are present on the surfaces of primary particles of the lithium nickel-containing composite oxide according to any one of claims 1 to 4. Positive electrode active material for lithium-ion secondary batteries.

10. The positive electrode active material for a lithium ion secondary battery according to claim 9, wherein the lattice constant length in the c-axis direction in the crystal of the compound-coated lithium nickel-containing composite oxide containing W and Li, obtained by Rietveld analysis of X-ray diffraction, is in the range of 14.183 Å to 14.205 Å.

11. A positive electrode active material for a lithium ion secondary battery as described in claim 9 or 10, wherein the volume-based average particle size MV of the compound-coated lithium nickel-containing composite oxide containing W and Li is in the range of 5 μm to 30 μm.

Citation Information

Patent Citations

  • Positive electrode active material for nonaqueous electrolyte secondary battery and manufacturing method thereof and nonaqueous electrolyte secondary battery using positive electrode active material

    JP2012079464A

  • Nickel composite hydroxide particle and production method therefor, positive electrode active material for nonaqueous electrolyte secondary battery and production method therefor, and nonaqueous electrolyte secondary battery

    JP2014146441A

  • Positive electrode active material for nonaqueous electrolyte secondary batteries, manufacturing method thereof, and nonaqueous electrolyte secondary battery arranged by use of positive electrode active material

    JP2015216105A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery arranged by use thereof

    JP2017084513A

  • Nickel complex hydroxide particle and production method therefor, non-aqueous electrolyte secondary battery positive electrode active material and production method therefor, and non-aqueous electrolyte secondary battery

    WO2014115380A1